Speechace’s Action In Improving Pronounciation at Senior High School - Jihan Amelia Amin, Jihan Amelia Amin; Nurhamdah; Kalsum (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
The intent of the study was to examine the efficacy of using the Speech Ace program in enhancing the English pronunciation of senior high school. A pre-experimental approach was used, consisting of one experimental class that included Speech Ace during sessions that received standard education. Both courses underwent pre-testing and post-testing to assess their pronunciation abilities. The findings demonstrated a statistically significant enhancement in the average score of the experimental group's post- test, which increased from 64,85 to 74,38. On the other hand. A t-test analysis comparing independent samples showed a statistically significant difference between the groups, with a p-value of 0.000, which is less than the significance level of 0.05. As a result, it was determined that the study hypothesis was confirmed, indicating that SpeechAce had a considerable impact on students' English-pronunciation proficiency. The good evaluations of SpeechAce were also seen in the student interviews and surveys. In summary, the results of the study provide concrete evidence that using technology-based tools like SpeechAce may significantly improve students' pronunciation abilities when used with traditional teaching techniques.